PENGARUH PENGEMBANGAN KARIR DAN PELATIHAN TERHADAP RETENSI KARYAWAN DENGAN ORGANIZATIONAL CITIZENSHIP BEHAVIOUR (OCB) SEBAGAI VARIABEL MEDIATING (Studi Kasus di PT.Emanuel) - Freddy MS; Djoko Santoso (Jurnal Riset Ekonomi dan Bisnis, 2016)
This study aims to determine the effect of career development, training and OCB on the retention of employees; and examine the effect of organizational citizenship behavior in the relationship between career development, training and retention of employees. The study population and sample are sales employees in PT.Emanuel with a sample size of 80 respondents. The analytical method used in this research is multiple linear regression analysis using SPSS (Statistical Package for Social Science) version 20. Based on the analysis it was found that all the independent variables (career development, training, and organizational citizenship behavior) had a positive effect and significant to the dependent variable (employee retention). No contributions OCB intervening variables to improve employee retention and training in their jobs directly or indirectly. The results of this study indicate that the variables that most influence employee retention is a career development with a standard value of the coefficient of 0.500, training with a standard value of the coefficient of 0373 and organizational citizenship behavior with a standard value of the coefficient of 0172. The implications of the study for retaining employees is to increase career development, training regularly and maintain a positive individual behavior and independent and contribute to the company.